QUEBRANDO A BANCA – A PROBABILIDADE E OS CASSINOS - Campos, Celso Ribeiro; Wodewotzki, Maria Lucia Lorenzetti; Jacobini, Otávio Roberto; Ferreira, Denise Helena Lombardo (Prometeica - Revista de Filosofía y Ciencias, 2012)
QUEBRANDO A BANCA – A PROBABILIDADE E OS CASSINOSCELSO RIBEIRO CAMPOS, MARIA LUCIA LORENZETTI WODEWOTZKI, OTÁVIO ROBERTO JACOBINI DENISE HELENA LOMBARDO FERREIRA (UNESP, Brasil)